1992
DOI: 10.1111/j.1533-8525.1992.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Context of Race Differentials in Juvenile Justice Dispositions

Abstract: Proponents of traditional conflict theory have argued that minority races receive harsher justice system dispositions because they lack the power and resources to ensure equal treatment. Hawkins’ (1987) proposed revision of this model predicts minoritv races will receive harsher dispositions in social contexts in which their power threatens the dominant group's hegemony. This study uses juvenile justice processing data from the 32 Florida SMA counties to examine these competing models. The effects of three mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 34 publications
5
54
0
Order By: Relevance
“…There already exists a body of social scientific research on the prediction of dispositions, as well as some work on identifying biases in dispositions and assessments (Bridges & Steen 1998;Carter 1979;Dannefer & Schutt 1982;Frazier, Bishop & Henretta 1992;Gross 1967;Horowitz & Pottieger 1991;Horwitz & Wasserman 1980;Kowalski & Rickicki 1982;McCarthy & Smith 1986;Phillips & Dinitz 1982;Sanborn 1996;Thomas & Cage 1977;Teilman & Landry 1981;Thornberry 1973;Tittle & Curran 1988). It is rare, however, for research on discretionary court actions to intersect with research on juvenile recidivism (but see Minor, Hartmann and Terry 1997).…”
Section: Implications For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…There already exists a body of social scientific research on the prediction of dispositions, as well as some work on identifying biases in dispositions and assessments (Bridges & Steen 1998;Carter 1979;Dannefer & Schutt 1982;Frazier, Bishop & Henretta 1992;Gross 1967;Horowitz & Pottieger 1991;Horwitz & Wasserman 1980;Kowalski & Rickicki 1982;McCarthy & Smith 1986;Phillips & Dinitz 1982;Sanborn 1996;Thomas & Cage 1977;Teilman & Landry 1981;Thornberry 1973;Tittle & Curran 1988). It is rare, however, for research on discretionary court actions to intersect with research on juvenile recidivism (but see Minor, Hartmann and Terry 1997).…”
Section: Implications For Researchmentioning
confidence: 99%
“…Findings are mixed, with some studies concluding that race and gender have profound influence on decisions to place youth (Frazier, Bishop & Henretta 1992;Horowitz & Pottieger 1991;McCarthy & Smith 1986;Thomas & Cage 1977;Thornberry 1973;Tittle & Curran 1988), and others finding no evidence of such bias (Carter 1979;Dannefer & Schutt 1982;Horwitz & Wasserman 1980;Kowalski & Rickicki 1982;Phillips & Dinitz 1982;Teilman & Landry 1981). I attempt to identify such bias in my own analyses.…”
mentioning
confidence: 99%
“…Research had pointed out that police routinely label African-American teenagers as delinquent and refer them to juvenile court disproportionately more than White teenagers when engaging in the same or similar behavior (Frazier, Bishop, & Henretta, 1992;Huizinga & Elliot, 1987;Staples, 1987;Thomas & Cage, 1977). Other studies found that African-American youth were at much higher risk of arrest than White youth (Tracy, Wolfgang, & Figlio, 1985).…”
Section: Introductionmentioning
confidence: 93%
“…Associated with claims of damaging subjectivity is the concern with marginalisation whereby 12 See also Frazier and Bishop (1995) who reported that juvenile justice officials used more severe sanctions where they perceived that minority families were incapable of providing good parental supervision. Where parents were expected to be interviewed by juvenile justice personnel, those without telephones, cars or with inflexible jobs were less accessible, and were implicitly deemed to be less capable of providing good parental supervision.…”
Section: Minority Criminologistsmentioning
confidence: 99%
“…The US approach could assist here. Frazier and Bishop (1995), for example, used their quantitative data -which showed that the 'race' of offender had an independent effect in formal juvenile justice system processing -to explore whether the results were consistent with officials' experiences in the juvenile justice system. The researchers gave a two-paragraph description of the quantitative findings to judges, prosecutors, public defenders, and intake supervisors, and asked them whether the findings were consistent with their experiences.…”
mentioning
confidence: 99%